Исследование управления диспетчером доступа к ресурсам информационной сети - Скомороха, Л. С. (ХНУРЭ, 2009)
This given work is devoted consideration of questions and methods of realization of mandatory and discretionary mechanisms of access control to the resources by additional facilities of protection from unauthorized access
Keywords: доступ к ресурсам информационной сети; информационная сеть